An (in-)coherent metamorphic evolution of high-P eclogites and their host rocks in the Chinese southwest Tianshan? - Meyer, Melanie; Klemd, Reiner; John, Timm; Gao, Jun; Menneken, Martina (Journal of Metamorphic Geology, 2016)
In the (ultra‐)high‐P–low‐T metamorphic terrane of the Chinese South Tianshan, discontinuous mafic blocks and boudins (former upper oceanic crust) are now embedded in voluminous (mainly metasedimentary) host rocks. Two different models were proposed and relate the occurrence of both high‐P and ultra‐high‐P mafic and metasedimentary rocks to either (i) a tectonic mélange style exhumation, with no exhumation of coherent units, but different lithologies derived from different depths juxtaposed and intermingled during exhumation in the subduction channel, or (ii) the evolution of two coherent metamorphic belts: one with high‐P and the other with ultra‐high‐P conditions. In contrast to most previous studies in the Chinese South Tianshan which focused either on single eclogites or metasedimentary rocks (assumed as representative), this study concentrates on the systematic investigation of both mafic boudins and their immediate sedimentary host rocks, because the investigation of both lithologies and the comparison of their metamorphic evolution is crucial to reconstruct the geodynamical context of the whole (ultra‐)high‐P–low‐T metamorphic complex. Several sample pairs consisting of both lithologies were geochemically investigated and their respective metamorphic evolution was reconstructed using geothermobarometry and thermodynamic modelling. The latter approach considers changes in the mineral assemblage during the metamorphic evolution, as well as changes in mineral composition, which may help to determine the metamorphic history of a rock despite the preservation of critical mineral assemblages. All samples experienced a clockwise P–Tpath with overall maximum P–T conditions of 540–550 °C and 1.9–2.25 GPa for the host rocks, and 555–575 °C and 2.2–2.5 GPa for the eclogites. Peak‐metamorphic temperatures of 525–540 °C of the metasedimentary host rocks were also confirmed by Raman spectroscopy of carbonaceous material. Results from thermobarometry and thermodynamic modelling are consistent with the observation that none of the samples contains mineral relicts indicating UHP conditions (like coesite in garnet) and neither conventional thermobarometry, nor thermodynamical modelling resulted in P–Tconditions in the stability field of coesite. Thus, no evidence of ultra‐high‐P conditions was found. Given that the whole sampled river valley lies within the proposed ‘ultra‐high‐P sub‐belt’ and considering former studies, which showed that at other places within this ‘unit’ both ultra‐high‐P and high‐P rocks are now juxtaposed on a small scale, the formation of the whole (ultra‐)high‐P–low‐T metamorphic belt in the Chinese South Tianshan as a tectonic mélange style exhumation is more convincing than the formation and juxtaposition of two coherent metamorphic units with high‐P and ultra‐high‐Pconditions respectively.<br
Keywords: (U)HP metamorphism; eclogite; P–T path; thermobarometry; Tianshan

Coexisting carbonate-bearing eclogite and blueschist in SW Tianshan, China: Petrology and phase equilibria. - Li, Jilei; Klemd, Reiner; Gao, Jun; Meyer, Melanie (Journal of Asian Earth Sciences, 2012)
Carbonate-bearing eclogite and blueschist coexist in the same lithological sequence in the Tianshan (ultra-)high-pressure/low-temperature metamorphic belt, northwestern China. Both of them consist of the mineral assemblage garnet+omphacite+dolomite±magnesite+phengite±paragonite+epidote/clinozoisite+glaucophane±barroisite/(Mg-)katophorite+rutile/titanite+pyrite. The eclogite has an omphacite content of ca. 43vol.% and a glaucophane content of <1vol.%. In contrast, the blueschist has an omphacite content of <8vol.% and a glaucophane content of ca. 43vol.%. The blueschist occurs as bands or interlayers in the eclogite. Lawsonite pseudomorphs of epidote/clinozoisite+paragonite assemblages in garnet are commonly observed in the eclogite and blueschist. High carbonate contents in oceanic metabasalts suggest that the precursor basaltic crust has undergone significant hydrothermal alteration prior to subduction. Mineral assemblages and textures show that the omphacite-carbonate-bearing blueschist and the carbonate-bearing eclogite underwent an identical metamorphic evolution. Phase equilibrium modeling in the TiNCaKFMASCHO system further indicates that both the carbonate-bearing eclogite and the omphacite-bearing blueschist equilibrated at peak metamorphic conditions of 540-565°C and 21.8-23.1kbar. Under these conditions calculated X CO2 isopleths reveal the presence of a mainly aqueous fluid phase (X CO20.02) for the coexisting eclogite and omphacite-bearing blueschist. The stability of the high-pressure mineral assemblages in the eclogite and the omphacite-bearing blueschist is due to differences of the respective bulk-rock composition (the CaO content in particular). This study suggests that three different kinds of blueschist were formed during subduction and exhumation of the South Tianshan oceanic crust, including prograde blueschist formed prior to eclogitization, retrograde blueschist formed by rehydration of eclogite during exhumation in the subduction channel, and coexisting blueschist with eclogite under peak metamorphic conditions. © 2012 Elsevier Ltd.
UnivIS-Import:2015-03-09:Pub.2012.nat.dgeo.IGM.c3geoc.coexis
Keywords: Coexistence; Eclogite; Omphacite-bearing blueschist; Pseudosection; Tianshan (ultra-)high-pressure/low-temperature belt

Compositional zoning in dolomite from lawsonite-bearing eclogite (SW Tianshan, China): Evidence for prograde metamorphism during subduction of oceanic crust. - Li, Jilei; Klemd, Reiner; Gao, Jun; Meyer, Melanie (American Mineralogist, 2014)
Dolomite with compositional zoning was discovered in carbonate-lawsonite- bearing eclogites in the Tianshan (ultra-)high-pressure/low-temperature metamorphic belt, northwestern China. The eclogite-facies dolomite occurs as matrix porphyroblast and as inclusion in garnet, both of which display the same chemical zoning pattern. The dolomite contains inclusions of calcite (probably after aragonite), magnesite, glaucophane, lawsonite (and its pseudomorphs), allanite, epidote, paragonite, phengite, and omphacite. The chemical zoning in dolomite is well defined by a continuous core-to-rim Mg increase and Fe-Mn decrease. The concentrations of transition metal elements, REE, and Y also decrease from core to rim of the dolomite. Thermodynamic modeling demonstrates that the Fe-Mg zoning of dolomite is largely temperature dependent and, thus, is interpreted as prograde growth zoning, which developed during subduction of carbonate-bearing oceanic crust. It is suggested that dolomite in equilibrium with garnet formed as a result of changing matrix compositions due to increasing temperatures. In addition, thermodynamic modeling demonstrates that during subduction at high-pressure conditions prograde-formed aragonite and dolomite were transformed to dolomite and magnesite. Furthermore, Fe-rich magnesite inclusions in matrix dolomite and in dolomite inclusions in garnet are shown to have formed during high-pressure conditions prior to peak metamorphic conditions and, therefore caution is warranted using Fe-bearing magnesite occurrences in eclogite-facies rocks as an unambiguous ultrahigh pressure indicator as previously suggested. © 1997 - 2014 Mineralogical Society of America. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2014.nat.dgeo.IGM.c3geoc.compos_1
Keywords: Dolomite; Eclogite; High pressure; Magnesite; Prograde zoning; Tianshan

High-pressure mafic oceanic rocks from the Makbal Complex, Tianshan Mountains (Kazakhstan & Kyrgyzstan): Implications for the metamorphic evolution of a fossil subduction zone. - Meyer, Melanie; Klemd, Reiner; Konopelko, Dmitry (Lithos, 2013)
The Makbal Complex in the western Tianshan Mountains of Kazakhstan and Kyrgyzstan consists of HP/UHP metasedimentary host rocks which enclose various HP mafic blocks or boudins. These mafic rocks comprise rare eclogites (sensu stricto and sensu lato), garnet amphibolites (retrograded eclogites) and a newly discovered glaucophanite (glaucophane-garnet-omphacite bearing rock).So far the Makbal Complex has been interpreted to predominantly consist of continental lithologies and the mafic rocks were considered as dismembered dikes intruding continental metasediments. This interpretation is mainly based on the geological relationship and bulk rock chemistry of the different rock types. It was further suggested that the continental lithologies of the Makbal Complex underwent eclogite-facies metamorphism in a former subduction zone.In the present study we combined conventional geothermometry, P-T pseudosection modeling and major and trace element whole rock geochemistry for different mafic samples (glaucophanite and eclogites (sensu lato)) in order to shed light on both the metamorphic evolution and the protoliths of the mafic HP rocks in the Makbal Complex.Prograde to peak-pressure clockwise P-T paths of glaucophanite and eclogites (sensu lato) were modeled using garnet isopleth thermobarometry. The results show that the glaucophanite and eclogite (sensu lato) samples experienced similar prograde P-T paths and slightly different peak metamorphic conditions at . 560. °C at 2.4. GPa for the former and between . 520. °C at 2.2. GPa and . 555. °C at . 2.5. GPa for the latter, corresponding to burial depths between 70 and 85. km.Whole rock major and trace element analyses and petrological evidence imply that the various rock types at the Makbal Complex most likely originated from different precursor rocks. Eclogites (sensu lato) are believed to represent strongly retrogressed former eclogite-facies rocks that had never been eclogites (sensu stricto, i.e. >70 vol.% garnet and omphacite) due to an unfavorable alkali-poor bulk composition (Na2O <1wt.%). The four high-pressure mafic samples investigated in this study originated from oceanic crust (Zr/Hf ratio of 33 to 35) which contradicts all previous studies suggesting a continental protolith for all mafic HP/UHP rocks at Makbal.The present study indicates that the mafic high-pressure rocks represent incoherent segments of exhumed oceanic crust. Juxtaposition of different mafic oceanic (this study) and continental rocks is suggested to be due to buoyancy-driven exhumation of the metasedimentary host rock in the subduction channel where dismembered fragments of the subducted oceanic crust were captured in different depths. © 2013 Elsevier B.V.
UnivIS-Import:2015-03-09:Pub.2013.nat.dgeo.IGM.c3geoc.highpr
Keywords: Garnet isopleth thermobarometry; Makbal HP/UHP Complex; P-T pseudosection; Thermobarometry; Tianshan Mountains

Metamorphic evolution of (ultra)-high-pressure subduction-related transient crust in the South Tianshan Orogen (Central Asian Orogenic Belt): Geodynamic implications - Klemd, Reiner; Gao, Jun; Li, Jilei; Meyer, Melanie (Gondwana Research, 2015)
The study of subduction-related high-pressure- and ultra-high-pressure metamorphic rocks exposed in orogenic belts is critical for unraveling the tectonothermal evolution of an orogen. The South Tianshan Orogen of the southwestern Central Asian Orogenic Belt, one of the world's largest accretionary orogens, contains several Paleozoic (ultra-)high-pressure ((U)HP) metamorphic terranes. (U)HP eclogites, blueschists and associated (U)HP metasedimentary rocks of continental and oceanic origin were reported from two localities in the Northern Tianshan (NTS) of Kazakhstanand Kyrgyzstan, namely from the Ordovician Aktyuz and Makbal metamorphic terranes. Furthermore Lower Carboniferous (U)HP eclogites and blueschists of oceanic origin are located in the Southern Tianshan Accretionary Complex (STAC) of southern Kyrgyzstan (Atbashi) and northwestern China (Akeyazi). The continentally-derived Aktyuz eclogite is considered to have experienced a continuous clockwise prograde P–T path with peak metamorphic conditions of ca. 1.6–2.1 GPa at 610–670 °C, corresponding to a burial depth of about 70 km. A peak metamorphic Lu–Hf garnet isochron age of 474 ± 2 Ma for the retrogressed eclogite of continental origin is in accordance with a Sm–Nd garnet isochron age of 462 ± 7 Ma interpreted as time of cooling and decompression of the metamorphic rock assemblage below 650 to 600 °C. Quantitative P–T pseudosection modeling for peripheral Makbal HP garnet amphibolites of continental origin also revealed a continuous clockwise P–T path with peak-metamorphic conditions of ca. 1.4 GPa at ca. 620 °C followed by an isothermal uplift to ca. 0.7 GPa. Furthermore, prograde P–T paths of oceanically-derived central Makbal high-pressure metabasic rocks revealed peak metamorphic conditions between 520 °C and 560 °C at 2.2 GPa to 2.5 GPa with subsequent isothermal decompressions. The metamorphic (P–T) evolution of a garnet–chloritoid–talc schist is exhibited by a P–T trajectory starting ca. 480 °C at 2.5 GPa, followed by peak pressures of ca. 2.85 GPa at 525 °C and peak temperatures of ca. 580 °C at 2.4 GPa. A Lu–Hf peak metamorphic age of 470.1 ± 2.5 Ma for a peripheral garnet amphibolite is in accordance with a garnet-growth Sm–Nd age of 475 ± 4 Ma of the UHP garnet–chloritoid–talc schist. Different and variable P–T paths show that former oceanic and continental crust at Makbal was subducted to different maximum depths (HP versus UHP conditions). The (U)HP metamorphism of oceanic and continental mafic rocks from the Aktyuz and Makbal metamorphic terranes is assumed to have occurred in a similar time frame of between 500 and 460 Ma. The proposed geodynamic model for the HP Aktyuz metamorphic terrane incorporates the deep northeast-directed subduction of NTS continental crust under the Ankrakhai block of Paleo-Kazakhstan subsequent to the closure of the Djalair–Naiman Basin. At Makbal the final consumption of the oceanic crust of the Terskey Ocean to the northeast was immediately followed by the deep subduction of a (thinned) passive continental margin of the Central Tianshan Arc Terrane (CTA). Both scenarios are in accordance with continental-type subduction geodynamics producing the subduction-related (U)HP rocks during continental–continental collision processes. The exhumation of detached oceanic material by channel flow may have been initiated by the transient subduction of oceanic and subsequent continental crust. The Lower Carboniferous (U)HP metamorphic terranes (Atbashi and Akeyazi) in the Southern Tianshan Accretionary Complex are mainly composed of metasediments which host some lenses and boudins of oceanically-derived blueschists and eclogites. Most eclogites, blueschists and metasediments have experienced peak high-pressure metamorphism (480–580 °C at 1.4–2.1 GPa), while some slices display UHP-conditions (2.7–3.3 GPa at 570–630 °C). Multi-point Lu–Hf and Sm–Nd isochrons from several eclogite and blueschist samples from the Atbashi and Akeyazi metamorphic terranes revealed consistent ages of ca. 320–315 Ma for the peak of metamorphism, thereby confirming that (U)HP metamorphism occurred during a single subduction event. The highly variable peak metamorphic conditions displayed by the (U)HP rocks imply that metamorphism of the metasediments and the various metabasic rocks occurred in different depths of the subduction zone. (U)HP metabasites and metasediments exhibit different P–T paths, which is consistent with the chaotic incorporation in a subduction channel resulting in the eventual exhumation as a mélange. This scenario is much in agreement with initial subduction of oceanic crust and accretionary wedge sediment removal by subduction erosion and thus is similar to accretionary-type subduction terranes, although, with higher peak P–T conditions than previously recorded. The absence of significant melting, in combination with the variable peak pressure metamorphic conditions and the intimate interlayering of high- and ultrahigh-pressure rocks, suggests that the (U)HP rocks were derived from varying depths within the subduction zone and then juxtaposed during exhumation in the subduction channel. This is in accordance with exhumation of the (U)HP rocks by channel flo
Keywords: South Tianshan Orogen; (Ultra-)high-pressure metamorphism; Geochronology; Accretionary- and continental-type subductions; Channel flow exhumation

Subduction and exhumation mechanisms of ultra-high and high-P oceanic and continental crust at Makbal (Tianshan, Kazakhstan and Kyrgyzstan) - Meyer, Melanie; Klemd, Reiner; Hegner, E.; Konopelko, Dmitry (Journal of Metamorphic Geology, 2014)
UnivIS-Import:2015-03-09:Pub.2014.nat.dgeo.IGM.c3geoc.subduc

The Fermi-LAT Lightcurve Repository - Abdollahi, S.; Ajello, M.; Baldini, Luca; Ballet, J.; Bastieri, D.; Becerra Gonzalez, J.; Bellazzini, R.; Berretta, A.; Bissaldi, E.; Bonino, R.; Brill, A.; Bruel, P.; et al. (Astrophysical Journal Supplement Series, 2023)
The Fermi Large Area Telescope (LAT) lightcurve repository (LCR) is a publicly available, continually updated library of gamma-ray lightcurves of variable Fermi-LAT sources generated over multiple timescales. The Fermi-LAT LCR aims to provide publication-quality lightcurves binned on timescales of 3, 7, and 30 days for 1525 sources deemed variable in the source catalog of the first 10 yr of Fermi-LAT observations. The repository consists of lightcurves generated through full likelihood analyses that model the sources and the surrounding region, providing fluxes and photon indices for each time bin. The LCR is intended as a resource for the time-domain and multimessenger communities by allowing users to search LAT data quickly to identify correlated variability and flaring emission episodes from gamma-ray sources. We describe the sample selection and analysis employed by the LCR and provide an overview of the associated data access portal.
CRIS-Team WoS Importer:2023-05-26